AMPER-Argentina: pretonemas en oraciones interrogativas absolutas - Gurlekian, Jorge (2009)
The present work belongs to project AMPER (Multimedia Atlas of Prosody of the Romanic Space). The dialectal area of study is the Spanish from Buenos Aires. This work analyses absolute interrogative sentences of the SVO-type: a NP (oxytone, paroxytone and proparoxytone heads), a VP (paroxytone head), a Prep. phrase (oxytone, paroxytone and proparoxytone heads). In addition, pretonemes are examined according to the intonation Autosegmental-metrical (AM) framework and the phonological phrase (f) influence is observed on the phonological representation of pitch accents. The pretoneme results indicate differences and not only one prosodic phrasing which may characterize this modality. The first peaks (P1) which belong to the first f do not show higher tones if compared to the P1 of declarative sentences. An initial frontier tone H% is discarded. These findings confirm a previous study: information regarding the absolute interrogative modality is out of the pretoneme, in the final toneme.